2011
DOI: 10.1517/13543784.2011.592830
|View full text |Cite
|
Sign up to set email alerts
|

Novel opioid antagonists for opioid-induced bowel dysfunction

Abstract: Two strategies effectively relieve OBD without interfering with centrally mediated analgesia: the administration of opioid antagonists with limited systemic absorption and peripherally acting mu-opioid receptor antagonists (PAMORA) that selectively target mu-receptors in the gastrointestinal tract. Methylnaltrexone and alvimopan are two recently marketed PAMORA and provide a new mechanism-based approach for the treatment of opioid-induced gastrointestinal dysfunction. However, its use in clinical practice is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 36 publications
0
63
0
1
Order By: Relevance
“…Full descriptions of these are beyond the scope of this review, and readers are referred to a number of reviews (Cicero, 1980;Reisine and Pasternak, 1996;Pattinson, 2008;Diego et al, 2009Diego et al, , 2011Cox, 2011;Elliott et al, 2011;Wald, 2012). However, it is worthwhile to highlight several aspects of these additional functions.…”
Section: E Other Actionsmentioning
confidence: 99%
“…Full descriptions of these are beyond the scope of this review, and readers are referred to a number of reviews (Cicero, 1980;Reisine and Pasternak, 1996;Pattinson, 2008;Diego et al, 2009Diego et al, , 2011Cox, 2011;Elliott et al, 2011;Wald, 2012). However, it is worthwhile to highlight several aspects of these additional functions.…”
Section: E Other Actionsmentioning
confidence: 99%
“…Together, these effects result in the formation of dry, hard stools that are difficult to pass. 2,14 Opioids may also inhibit bowel motility through immunomodulatory effects involving recruitment of leukocytes and production of inhibitory neurotransmitters, such as inducible nitric oxide. 1 In addition to these peripheral effects, opioids may decrease intestinal motility by stimulating central µ-opioid receptors, leading to changes in the autonomic outflow to the gut.…”
Section: Pathophysiology Of Oicmentioning
confidence: 99%
“…Two representative polymer conjugated opioid derivatives are shown in Figure 8. These compounds consist of naloxol analogs linked to PEG chains through hydrolytically stable ether linkage [71,72]. In preclinical studies, these pegylated opioid derivatives were found to maintain their centrally mediated analgesia, while antagonizing peripherally mediated constipation.…”
Section: Polymer-opioid Conjugates and Polymeric Opioid Derivativesmentioning
confidence: 99%